PENGARUH INSENTIF TERHADAP PRESTASI KERJA KARYAWAN BAGIAN PERGUDANGAN PADA PT.BUKIT ASAM (PERSERO) TBK TANJUNG ENIM - Jalaludin (Jurnal Manajemen dan Bisnis, 2021)
This study aims to knowing "Is there an incentive effect on employee performance Part Warehousing At PT. Bukit Asam (Persero) Tbk Tanjung Enim ". Discussion of the results obtained value b = 0,467, the value of b is the value of the variable incentive (X). After the value b obtained subsequent search for a value that is the value of work performance variables (Y) employees Part Warehousing At PT. Bukit Asam (Persero) Tbk Tanjung Enim. And obtained the simple linear regression equation is Y = 23.996 + 0.467 X. This value has meaning if incentives (X) increased 0,467 one unit then the job performance (Y) employees Part Warehousing At PT. Bukit Asam (Persero) Tbk Tanjung Enim will increase by 0,467. The results of the analysis obtained correlation coefficient r = 0.600. This means incentives (X) have positive influence and tightly enough on job performance (Y) employees Part Warehousing At PT. Bukit Asam (Persero) Tbk Tanjung Enim. The result of the analysis is terminated unknown coefficient value = 0.36 or 36% means that incentives (X) contribute to job performance (Y) by 36%. This means incentives of contributions or donations have strong enough on employee performance Part Warehousing At PT. Bukit Asam (Persero) Tbk Tanjung Enim and the remaining 64% are influenced by other factors not examined